Facile Synthesis of New Antiviral Fluoro-Quinazolines Enabled by Merging Domino Reactions - Kohlbauer, Sascha; Xia, Honglin; Grau, Benedikt W.; Wangen, Christina; Hahn, Friedrich; Nenajdenko, Valentine G.; Marschall, Manfred; Tsogoeva, Svetlana B. (Synthesis, 2024)
Quinazolines, particularly fluoro-quinazolines, represent important structural motifs in bioactive molecules and pharmaceuticals. Despite several known synthetic routes, the efficient synthesis of fluorine-containing quinazolines remains a challenge. Herein, the straightforward and sustainable synthesis of fluorine-substituted quinazolines using domino sequences is reported. The obtained novel fluoro-quinazoline compounds exhibit significant in vitro activity against human cytomegalovirus (HCMV), expanding the library of potential antiviral drug compounds. Our finding outlays the synthetic toolkit for fluoro-quinazolines and introduces new agents for HCMV therapy.
Keywords: domino reaction; one-pot reaction; heterocycles; fluoro-quinazolines; antiviral agents